Communicative Translation of Ecological Terms in Short Novel - Sahayu, Wening; Triyono, Sulis; Muslim, Ivan Bachrul (International Journal of Psychosocial Rehabilitation, 2020)
This study focus on how the ecological terms has been translated communicatively. The major data on this study conducted from every possible language units which is contains an ecological representative, words, phrases, clauses, and sentences in the translated short novel of The Old Man and The Sea by Ernest Hemingway. The study itself has various goals to obtain, regarding on how the translation can represents the whole contextual meaning, equivalence, text effect, and applicable message. Main objectives of this study existed on the obligation to represent a particular approach in order to analyzing the literal translation text concerning the various factors on how and why the translation of ecological terms can be equivalently understandable. Gaining the whole message in the preservation of environment, whereas the notion about translation dealing with ecological terms must be interfered by the translation process through communicative translation. The result of this study showed that there are two kinds of ecological terms has been translated communicatively. First, dealing with specific items or nature items and the second is dealing with the interaction between main character and the environment in the short novel.